QUALITY OF MECHANICAL SOYBEAN HARVESTING AT TWO TRAVEL SPEEDS - De Lima, Felipe B. F. [UNESP]; Da Silva, Michel A. F. [UNESP]; Da Silva, Rouverson P. [UNESP] (Soc Brasil Engenharia Agricola, 2017)
Soybean harvesting is the last operation performed in the field and therefore has high added value. Quantitative losses during this process should therefore be minimized to achieve maximum quality and increase the sustainability of the production system. The aim of the present study was to determine and characterize the quantitative losses and operational characteristics of an axial-flow combine harvester, using tools from Statistical Quality Control to determine the quality of the harvesting operation. The experiment was designed in accordance with the assumptions of statistical process control, with a total of 40 sampling points monitored over time. Quality indicators of harvester performance and crop agronomic characteristics were evaluated at two harvester travel speeds (5 and 7 km h(-1)). The stability of the process was confirmed for the variables indicated by the analysis of run charts for the variables engine water temperature at a travel speed of 5 km h(-1); engine oil pressure, fuel consumption and cutting height at a travel speed of 7 km h(-1); and losses at both speeds, indicating that these were only affected by natural causes.
Keywords: control charts; variability; harvesting losses